In situ expression and serum level of thymic stromal lymphopoietin in oral lichen planus. (14th June 2014) - Sun, Mingxia; Tan, Wanye; Liu, Shaohua; Liu, Guixiang; Zhang, Xiaoying; Wang, Ning; Qu, Xun; Wei, Fengcai
<x xml:space="preserve">Abstract</x> Background Oral lichen planus (OLP) is a chronic inflammatory disease of oral mucosa in which the CD8+ T cell‐mediated cytotoxicity is regarded as a major mechanism of pathogenesis. The main objective of this study is to investigate in situ expression and secretion of thymic stromal lymphopoietin (TSLP) in specimens and sera from patients with oral lichen planus. Methods Thirty‐six patients with OLP and 35 donors enrolled in specimen and serum collection. Immunohistochemical method and immunofluorescence double‐staining method were used to detect the expression of thymic stromal lymphopoietin and its receptor (TSLPR) together with CD8 in OLP specimens. Enzyme‐linked immunosorbent assay (ELISA) was used to detect TSLP secretion. Results More TSLP‐ or TSLPR‐positive cells showed in OLP specimens than in normal controls, and TSLP‐positive cells were mainly in the epithelium, while TSLPR‐positive cells mainly in the lamina propria. Furthermore, the number of TSLP‐positive cells in the stratum basal was associated with the amount of mononuclear cells infiltrating in the lamina propria of OLP specimens. Among infiltrating mononuclear cells in the lamina propria, some CD8‐positive cells also expressed TSLPR. The TSLP serum level of patients with OLP was significantly higher than of healthy donors, but there was no statistically difference between two clinical subtypes of OLP. Conclusions Our findings provided the first evidence that TSLP may enroll in the pathology of OLP and the TSLP–TSLPR interaction may play an important role in it.